Soil Fertility Appraisal for Hot Arid Regions of Thar Desert, Rajasthan, India - Kumar, Mahesh; Raina, P; Singh, S K (Annals of Arid Zone, 2020)
Soil fertility assessment for hot arid regions of Thar Desert in the Indian state of Rajasthan was carried out and on the basis of fertility ratings the soils were classified as low, medium and high. In the present assessment a systematic set of 5655 geo-referenced soil samples across the land use systems viz. rainfed croplands, irrigated croplands and rangelands covering 12 districts of hot arid Rajasthan were collected. The soil samples were analyzed for pH, EC, soil organic carbon (SOC), available P, available K, available Fe, Zn Cu, and Mn. Results of the soil analysis revealed that SOC is low throughout the region, while available P was low to medium, but generally medium to high in available K. Among the micronutrients Cu and Mn were adequately supplied in most areas, but Zn and Fe were inadequate in large parts. As a whole, SOC, P, Fe and Zn are the major nutrients constraint in hot arid regions of Rajasthan that warrants the attention for development and implementation of soil test based nutrient management plans and application of corresponding nutrients. The Nutrient Index Values (NIV) was low for available P (1.61) and medium for available K (2.14). Amongst the micronutrients NIV for DTPA Zn (1.51) was low, marginal for Fe (1.67), adequate for Cu (2.14) and high for Mn (2.47). The wide spread deficiencies of P, Fe and Zn were most revealing; their deficiencies varies with districts and land use pattern. Irrigated croplands were better endowed than other land uses in respect of SOC, P, Zn and Cu; rangelands in respect of K and Fe, and rainfed croplands in respect of Mn. Key words: Hot arid Rajasthan, major nutrients, micro-nutrients, deficiency, nutrient index value.